Cerebrospinal fluid biomarkers of superficial siderosis in patients with spontaneous intracranial hypotension. (19th October 2022) - Häni, Levin; Fung, Christian; Jesse, Christopher Marvin; Schild, Christof; Piechowiak, Eike Immo; Dobrocky, Tomas; Raabe, Andreas; Beck, Jürgen
Abstract: Background and purpose: Spontaneous intracranial hypotension (SIH) is an important etiology of infratentorial superficial siderosis (iSS) of the central nervous system. However, the prevalence of iSS amongst patients with SIH is unknown and the imaging findings of iSS might represent a late stage of disease. The aim was to identify cerebrospinal fluid (CSF) biomarkers of iSS in patients with SIH. Methods: Consecutive patients evaluated for SIH at our institution between May 2017 and January 2019 were included. Lumbar CSF samples were analyzed for the presence of ferritin and bilirubin. Magnetic resonance imaging was assessed for the presence of iSS. Results: Twenty‐four patients with SIH were included. CSF samples were positive for bilirubin in 2/19 (10.5%). CSF ferritin was elevated in 7/23 (30.4%). Signs of iSS on imaging were present in four patients (16.7%). All patients with imaging signs of iSS demonstrated elevated CSF ferritin. Ferritin level was significantly higher amongst patients demonstrating iSS compared to those without (median 45.0 vs. 11.0 μg/l; p = 0.003). Symptom duration was longer in patients with iSS than in patients without iSS (median 40 months vs. 9 months, p = 0.018). Conclusion: Cerebrospinal fluid alterations indicative of iSS are prevalent amongst patients with SIH. It is speculated that a preclinical phase without symptoms or imaging signs but during which elevated biomarkers of the disease are apparent from CSF analysis might exist. It is suggested that measurement of CSF ferritin is incorporated in the work‐up of patients with SIH to identify those at risk of developing iSS. Abstract : Cerebrospinal fluid (CSF) alterations indicative of infratentorial superficial siderosis are prevalent amongst patients with SIH. It is speculated that a preclinical phase without symptoms or imaging signs but during which elevated biomarkers of the disease are apparent from CSF analysis might exist.